2011
DOI: 10.1007/s00405-011-1572-4
|View full text |Cite
|
Sign up to set email alerts
|

Double probe pH-monitoring findings in patients with benign lesions of the true vocal folds: comparison with typical GERD and the effect of smoking

Abstract: We conducted a pH-monitoring study to determine the prevalence of pathologic gastroesophageal reflux (GER+) and laryngopharyngeal reflux (LPR+) in patients with resected benign true vocal fold lesions (TVFLs) and positive reflux finding score (RFS). We compared our findings with those of patients with typical GER disease (GERD) symptoms and normal laryngoscopy. In the group of patients with TVFLs, we compared the pH-monitoring findings of smokers with those of non-smokers. Seventy-two [females 32, mean (SD) ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 28 publications
2
37
0
1
Order By: Relevance
“…In the study of Kuhn et al, LPR was identified in 64% of nodule patients and 18% of control subjects . This relationship between LPR and nodules has been supported by Beltis et al, who assessed the prevalence of LPR in patients with nodules compared to patients suffering from GERD . According to pH monitoring findings that differentiated distal reflux alone (GERD) from those who had proximal reflux (LPR), these authors reported a nodule rate of 60% in patients with LPR, double the rate of nodules in the GERD group.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…In the study of Kuhn et al, LPR was identified in 64% of nodule patients and 18% of control subjects . This relationship between LPR and nodules has been supported by Beltis et al, who assessed the prevalence of LPR in patients with nodules compared to patients suffering from GERD . According to pH monitoring findings that differentiated distal reflux alone (GERD) from those who had proximal reflux (LPR), these authors reported a nodule rate of 60% in patients with LPR, double the rate of nodules in the GERD group.…”
Section: Resultsmentioning
confidence: 82%
“…Five studies investigated the relationship between LPR and nodules using an objective approach to LPR diagnosis . In 1998 and 1999, respectively, Kuhn et al and Ulualp et al reported a significantly higher prevalence of pharyngeal acid reflux events in patients with nodules in comparison with healthy subjects .…”
Section: Resultsmentioning
confidence: 99%
“…Mevcut bulgular m z n sigara kullan m ndan bams z olarak incelenmi olmas na ra men özellikle reinke ödemindeki da l m n de i memi olmas n n temel nedenlerinden birinin, sigaraya ba l reinke ödemi olu umunun y llar süren bir döngüde olu tu unu ve ilerleyen dekadlarda anlaml fark olu turabilecek bir örnekleme ula abileceimiz oldu unu dü ünmekteyiz. Bununla birlikte laringofaringeal reflü-nün de benign kord vokal lezyonlarn n olu umunda rol oynad fakat sigaran n sinerjistik bir etkiyle de il kendi ba na bir faktör oldu u da literatürde bildirilmi tir (8).…”
Section: Tarti Maunclassified
“…1,2 Now, this leukoplakia of vocal fold is considered to be a premalignant lesion. Although many efforts have been contributed to treat the disease, results are still not satisfactory.…”
Section: Introductionmentioning
confidence: 99%